(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the fundamental nature of vowels and the various ways they are modified in speech. Vowels are defined as sounds produced without significant obstruction in the vocal tract, and their classification is based on tongue height, backness, and lip rounding. The text discusses key modifications such as length variation, quality shifts, reduction, nasality, and vowel harmony, highlighting their roles in language differentiation and evolution. Examples from languages like English, Finnish, French, and Turkish illustrate these concepts in action.